The Eastern Mediterranean Policy Of Russia in the Context Of Its Goal To Become A Great Power - Üren, Mustafa (Fırat University, 2021)
Being at the focal point of geopolitical theories, the Mediterranean is one region where global competition continues uninterrupted throughout history. Since Peter the Great, Russia, which has seen itself as a great power candidate, wants to reach the Eastern Mediterranean, which it regards as the hot sea, and part of the region's competition. Despite this request, she could not have reached her goal of occupying Istanbul by defeating the Ottoman Empire, and in no way reached the Eastern Mediterranean. The Soviet Administration, which came to power by overthrowing the Tsarist regime, did not give up its' goals but realized that it was impossible to have the Turkish Straits and put the strategy of obtaining a permanent military base in the region into effect. In this context, a military base was acquired in Syria, but it became necessary to be withdrawn from the region after losing the Cold War. Russia, which strengthened its power in the country and its' near abroad after the withdrawal, returned to the Eastern Mediterranean region and the Middle East region as of the mid-2000s with the claim of being a great power. In such a case, the question arises whether Russia, who has failed twice, will succeed this time. In this study, in which the answer to the subject in question will be sought, great importance was attached to reflecting the views of all parties, including Russia, to reach a correct conclusion. At the result of the analysis as a summary, it was concluded that no factor could prevent Russia from being permanent in the region, but it did not have the ability to fulfill the great power's tasks with its current capability.

Jeopolitik teorilerin odak noktasında yer alan Akdeniz, tarihsel süreçte küresel rekabetin kesintisiz devam ettiği bölgelerin başında yer almaktadır. I. Petro’dan beri kendisini büyük güç adayı olarak gören Rusya, sıcak deniz olarak kabul ettiği Doğu Akdeniz’e ulaşmayı ve buradaki rekabete dahil olmayı istemesine rağmen Osmanlı İmparatorluğu’nu yenerek İstanbul’u işgal etme ve bu sayede Doğu Akdeniz’e ulaşma hedefine ulaşamamıştır. Çarlık rejimini yıkarak iş başına gelen Sovyet Yönetimi, bu hedeflerinden vazgeçmemiş, ancak Türk Boğazlarını elde etmenin mümkün olmadığını görerek, bölgede kalıcı askeri üs elde etme stratejisini devreye sokmuştur. Bu kapsamda Suriye’de bir askeri üs elde edilmiş, fakat Soğuk Savaş’ın kaybedilmesinin ardından bölgeden geri çekilmek zorunda kalmıştır. Geri çekilme sonrasında ülke içi ve yakın çevresinde gücünü pekiştiren Rusya, büyük güç olduğu iddiasıyla 2000’li yılların ortalarından itibaren Orta Doğu bölgesine olduğu gibi Doğu Akdeniz bölgesine de geri dönmüştür. “Bu süreçte iki kez başarılı olamayan Rusya bu sefer başarılı olabilecek midir?” sorusunun cevabının aranacağı bu çalışmada, doğru bir sonuca ulaşabilmek için başta Rusya olmak üzere tüm tarafların görüşlerinin yansıtılmasına önem verilmiştir. Yapılan analiz neticesinde, bölgede Rusya’nın kalıcı olmasını engelleyebilecek bir faktörün olmadığı, ancak mevcut gücüyle büyük güçten beklenebilecek işlevleri yerine getirme yeterliliğine de sahip olmadığı sonucuna varılmıştır.
KÜRESEL GÜÇ OLMA HEDEFİ BAĞLAMINDA RUSYA'NIN DOĞU AKDENİZ POLİTİKASI